PENGEMBANGAN AWETAN ARTHROPODA DILENGKAPI POCKET BOOK SEBAGAI MEDIA PEMBELAJARAN DI KELAS X SMAN 3 GOWA - Rasdiyanah Jusman; St. Syamsudduha; Ainul Uyuni Taufiq (Department of Biology Education of Universitas Islam Negeri Alauddin Makassar, 2019)
This study aims to develop learning media aways arthropoda equipped with pocket book and determine the level of validity, practicality, and effectiveness of arthropod-preserved equipped with pocket book developed. This research and development refers to the 4D development model which includes four stages, namely define, design, develop , and disseminate. The research instrument is a validation sheet to obtain product validity data, questionnaire responses of students to get practicality data products, as well as test items to get product effectiveness data. Based on the results of epert validator research, the level of validity of learning media aways arthropoda is in the valid category with an average value 3,45. Based on the results of the students response to the practicality level of learning media is on the category is very positive with an average total value 3,75. Based on the test results of the students learning media awetan arthropoda equipped with pocket book is categorized effevtive because is reaches 81,02%.